2000
DOI: 10.1054/bjoc.1999.0884
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of unresectable, locally advanced pancreatic adenocarcinoma with combined radiochemotherapy with 5-fluorouracil, leucovorin and cisplatin

Abstract: The aim of the study was to evaluate the effectiveness and safety of a combined treatment modality including systemic chemotherapy with 5-fluorouracil (FU), leucovorin, cisplatin and external beam radiotherapy in patients with locally advanced pancreatic cancer. Systemic chemotherapy consisted of FU 400 mg m −2 and leucovorin 20 mgm −2 both given as intravenous bolus injection on days 1–4, plus cisplatin 20 mgm −2 administered as 90-min infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 28 publications
(23 reference statements)
1
20
0
2
Order By: Relevance
“…The complete response has continued for 36 months after the initial surgery. , 1996), leucovorin (Oman, Blind, Naredi et al, 2001;Huguier, Barrier, Valinas et al, 2001;Oettle, Arning, Pelzer et al, 2000;Andre, Balosso, Louvet et al, 2000;Kornek, Schratter-Sehn, Marczell et al, 2000;Link, Formentini, Papachristov et al, 1997;Raderer, Kornek, Hejna et al, 1997) and interferons were used with 5-FU as biochemical modulators, and epirubicin (Raderer , Kornek, Hejna et al, 1997), mitomycin, cyclophosphamide and many other agents were used in an attempt to gain synergistic effects . Weekly 5-FU with leucovorin, daily dipyridamole and intermittent mitomycin-C was reported to be effective palliative, neoadjuvant and adjuvant chemotherapy for pancreatic cancer Todd, Gloor, Lane et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete response has continued for 36 months after the initial surgery. , 1996), leucovorin (Oman, Blind, Naredi et al, 2001;Huguier, Barrier, Valinas et al, 2001;Oettle, Arning, Pelzer et al, 2000;Andre, Balosso, Louvet et al, 2000;Kornek, Schratter-Sehn, Marczell et al, 2000;Link, Formentini, Papachristov et al, 1997;Raderer, Kornek, Hejna et al, 1997) and interferons were used with 5-FU as biochemical modulators, and epirubicin (Raderer , Kornek, Hejna et al, 1997), mitomycin, cyclophosphamide and many other agents were used in an attempt to gain synergistic effects . Weekly 5-FU with leucovorin, daily dipyridamole and intermittent mitomycin-C was reported to be effective palliative, neoadjuvant and adjuvant chemotherapy for pancreatic cancer Todd, Gloor, Lane et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Systemic chemotherapy is an alternative treatment for patients with advanced and unresectable pancreatic cancer and many clinical trials have been performed in an attempt to find the optimal anti-cancer drug regimen. The combination of 5-FU and leucovorin has been shown to have some anti-cancer effect in patients with advanced gastrointestinal and pancreatic cancer (Oman, Blind, Naredi et al, 2001;Huguier, Barrier, Valinas et al, 2001;Oettle, Arning, Pelzer et al, 2000;Andre, Balosso, Louvet et al, 2000;Kornek, Schratter-Sehn, Marczell et al, 2000). However, the results for pancreatic cancer were far from satisfactory with a maximal response rate of 20-30% with either mono-or combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The data indicate that younger patients with good performance status, or treatment with gemcitabine-or capecitabine-based chemotherapy were favorable prognostic factors [35][36][37][38]. Multiple factors were analyzed using the log-rank single factor model, and the data suggested that patients who actually received a D 90 higher than 110 Gy and patients younger than 60 years may survive longer (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A Tabela 4 mostra um levantamento da literatura a respeito, mostrando a sobrevida atuarial mediana variando de 5,7 meses a 14 meses e 0% a 18% dos pacientes como sobreviventes a longo prazo (mais de dois anos de sobrevida) 10,13,17,24,[26][27][28][29][30] . Embora a maioria destes estudos sugira haver benefício na introdução do tratamento adjuvante, um estudo multicêntrico francês concluiu que a radioterapia, mesmo aplicada em altas doses (60 Gy no caso) e associada à quimioterapia com cis-diaminodicloro-platina, teve um pequeno impacto no controle local do tumor e na sobrevida e somente um efeito moderado no alívio sintomático da dor 30 .…”
Section: Mesesunclassified